2018
DOI: 10.1029/2017jb015320
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Nonplanar Thrust Faults Governed by Various Friction Laws

Abstract: Large‐scale irregular geometry of a fault surface, such as seamounts and subducted oceanic plateaus, is a prevailing factor that introduces stress heterogeneity and affects rupture dynamics. However, dynamic ruptures are also controlled by the constitutive laws that describe how fault friction evolves. In this study, we explicitly incorporate nonplanar thrust fault geometry into a three‐dimensional finite element model to numerically simulate spontaneous dynamic rupture and explore how dynamic ruptures would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…However, these effects are not considered in this study, as their relevant parameters on the megathrust are poorly known and we do not know whether such mechanisms occurred during the Nicoya earthquake. Furthermore, numerical results based on velocity‐weakening law do not qualitatively differ with those using slip‐weakening law (Gabriel et al, ; Luo & Duan, ; Murphy et al, ). As such, our results derived from the linear slip‐weakening law should be, at least qualitatively, no different from those incorporating more complex effects, if relevant frictional parameters on the megathrust can be well constrained from independent observations.…”
Section: Discussionmentioning
confidence: 92%
“…However, these effects are not considered in this study, as their relevant parameters on the megathrust are poorly known and we do not know whether such mechanisms occurred during the Nicoya earthquake. Furthermore, numerical results based on velocity‐weakening law do not qualitatively differ with those using slip‐weakening law (Gabriel et al, ; Luo & Duan, ; Murphy et al, ). As such, our results derived from the linear slip‐weakening law should be, at least qualitatively, no different from those incorporating more complex effects, if relevant frictional parameters on the megathrust can be well constrained from independent observations.…”
Section: Discussionmentioning
confidence: 92%
“…It has been found that models using rate‐weakening laws do not qualitatively differ with those using the LSW law (Bizzarri et al, 2001; Luo & Duan, 2018). However, friction laws with exponential weakening curves result in a faster energy release at the onset of slip and therefore may produce slightly more energetic rupture fronts than may those based on the LSW law (Dunham, 2007; Luo & Duan, 2018; Ryan & Oglesby, 2014). If we adopt a rate‐weakening friction law to reproduce the rupture process of the 2012 Nicoya M w 7.6 earthquake, a slightly higher yield stress may be inferred.…”
Section: The Spatial Pattern Of Strength On the Nicoya Megathrustmentioning
confidence: 99%
“…In fact, geometrical complexity including steps (Duan & Oglesby, ; Harris et al, ; Hu et al, ), kinks (Kase & Day, ; Templeton et al, ), branching (Bhat et al, ; Kame et al, ), and roughness (Fang & Dunham, ; Luo & Duan, ; Yang et al, ) is common for earthquake faults in nature. The heterogeneities of fault surfaces, even small geometrical perturbations on planar faults, result in different dynamic rupture processes and then seismic radiation (Madariaga, ).…”
Section: Introductionmentioning
confidence: 99%